Thermally stratified flow of Jeffrey fluid with homogeneous-heterogeneous reactions and non-Fourier heat flux model. Issue 8 (August 2019) - Ijaz, M.; Ayub, M.
Abstract: This article investigates the mixed convective flow of Jeffrey fluid near the axisymmetric stagnation point over an inclined permeable stretching cylinder. Analysis subjected to Cattaneo-Christov heat flux, thermal stratification and homogeneous-heterogeneous reactions are accounted. Suitable transformations are employed to obtain nonlinear ordinary differential system. Non-dimensional system is computed by Homotopy technique. Graphs and tables are constructed to analyze the influence of different flow parameters on temperature, concentration and velocity fields. The interpretation of skin friction coefficient is deliberated. It is noticed from obtained results that temperature is a decreasing function of thermal stratification parameter. Reverse behaviour of concentration is witnessed for higher estimations of homogeneous and heterogeneous parameters. Numerical results are compared with previous published results and found to be in good agreement for special casesof the emerging parameters.